2015
DOI: 10.1016/j.cognition.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Parallel temporal dynamics in hierarchical cognitive control

Abstract: Cognitive control allows us to follow abstract rules in order to choose appropriate responses given our desired outcomes. Cognitive control is often conceptualized as a hierarchical decision process, wherein decisions made at higher, more abstract levels of control asymmetrically influence lower-level decisions. These influences could evolve sequentially across multiple levels of a hierarchical decision, consistent with much prior evidence for central bottlenecks and seriality in decision-making processes. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 68 publications
5
19
0
Order By: Relevance
“…One important question in this regard is to what degree higherlevel representations (i.e., chunks and chunk positions) and low-level representations (i.e., elements and element positions) are activated sequentially, such that the first are needed to initiate the latter. Alternatively, higher-level and lower-level representations could be activated in parallel, potentially constraining each other (Ranti et al, 2015). Our results indicate that information about the position of a chunk within the larger sequence is activated only at chunk transition points, presumably as a cue to retrieve the next chunk identity.…”
Section: Chunk-level Representationsmentioning
confidence: 81%
See 1 more Smart Citation
“…One important question in this regard is to what degree higherlevel representations (i.e., chunks and chunk positions) and low-level representations (i.e., elements and element positions) are activated sequentially, such that the first are needed to initiate the latter. Alternatively, higher-level and lower-level representations could be activated in parallel, potentially constraining each other (Ranti et al, 2015). Our results indicate that information about the position of a chunk within the larger sequence is activated only at chunk transition points, presumably as a cue to retrieve the next chunk identity.…”
Section: Chunk-level Representationsmentioning
confidence: 81%
“…Alternatively, higher-level codes may need to remain active while lower-level representations are being used-in order to ward off interference from competing chunks, or to maintain the ability to navigate within the overall control structure once within-chunk processing has completed (Ranti, Chatham, & Badre, 2015). Currently, no neural-level data are available to distinguish between these theoretical options.…”
Section: Introductionmentioning
confidence: 99%
“…Rule‐guided behavior of this type has long been the focus of study in cognitive control research, as it supports complex contingent action selection (Badre & D'Esposito, ; Badre et al., ; Chatham et al., ; Ranti, Chatham & Badre, ), learning and generalization (Badre & Frank, ; Badre, Kayser & D'Esposito, ; Botvinick, ; Collins & Frank, ; Frank & Badre, ), decision making (Badre, Doll, Long & Frank, ), fluid reasoning (Bunge, ; Speed, ), and planning (Koechlin, Corrado, Pietrini & Grafman, ). This host of skills is key to flexible thought and action and academic success.…”
Section: Introductionmentioning
confidence: 99%
“…elements and element positions) are activated sequentially, such that the first are needed to initiate the latter. Alternatively, higher level and lower level representations could be activated in parallel, potentially constraining each other, as ( Ranti et al, 2015 ) have shown in the context of a paradigm where changes on different hierarchical levels were probed through explicit cues, rather than sequential context. Our results indicate that information about the position of a chunk within the larger sequence is activated only at chunk transition points, presumably as a cue to retrieve the next chunk identity.…”
Section: Discussionmentioning
confidence: 99%